Atopic dermatitis: clinical phenotypes, persistence and comorbidity - O.P. Volosovets; S.P. Kryvopustov; O.V. Mozyrskaya (Zaslavsky O.Yu., 2021)
Background. Atopic dermatitis is the most common skin disease among children. Its natural history is heterogeneous with a difference in age of manifestation, localization of lesions, severity, sensitization profiles, presence of comorbid atopic conditions, and longitudinal trajectories of disease progression. The study aimed to assess the impact of factors such as the onset of the disease, atopic family history, presence of concomitant allergic pathology, duration of breastfeeding on the course of the disease and the development of respiratory allergies, and the impact of environmental factors that aggravate the disease. Materials and methods. Children with atopic dermatitis (n = 88) were included in the study from September 2020 to April 2021 in Kyiv, Ukraine. Symptoms of respiratory allergy in the history of patients have been documented as comorbidity. Results. Total of 88 patients at the time of examination presented with manifestations of atopic dermatitis in the form of a rash, dry skin, scaling, itching, lichenization. The disease severity was significantly related to the age of onset: children with early phenotype had more severe disease (OR = 16.261; 2.056-127.911). There was no statistically significant association of early phenotype of atopic dermatitis with the development of concomitant allergic diseases (OR = 1.813; 0.415-7.916). A severe course was observed in the group of children with atopic family history (OR = 2.750; 1.123-6.735). Children with severe atopic dermatitis had a high risk of concomitant respiratory allergy (OR = 5.604; 1.863-16.863). The duration of breastfeeding did not impact the severity of atopic dermatitis (OR = 0.778; 0.119-5.100) and the risk of concomitant atopic diseases (OR = 1.417; 0.444-4.521). The course of atopic dermatitis was influenced by seasonality in 76 children (86.4 %): the condition of the skin deteriorated in the winter. Contact with the animal was associated with exacerbation of atopic dermatitis in 4 (4.5 %) children, food ingestion - in 20 children (25 %), pollen trees and grasses caused exacerbation in 5 children (5.7 %). Conclusions. Children with a severe phenotype of atopic dermatitis are at risk of developing respiratory allergies. Patients with atopic dermatitis who develop symptoms at the age of under 2 years, as well as those with an atopic family history, are at high risk of developing a severe disease phenotype.